Toponymic representations of central african capitals in french-speaking literary narratives - (:unkn) unknown (My University, 2023)
Toponymic representations of central african capitals in french-speaking literary narratives.This study answers the following title: Toponymic representations of central African capital inFrench-speaking literary narratives. By exploring the toponymic situation of three capital citiessuch as Libreville, Brazzaville and Yaoundé. This analysis examines the question of nameswhich has since been the subject matter of critical thinking in literature and human sciences.From the perspective of postcolonial studies and the semiotic of space, the reflection shedslight, not only on the stratified history, analogies and similarities through these three names,but also on the spatial reconfiguration that results from them. Organised around three mainparts, the first section is about the historiography notion of toponymy and names. The secondpart, as for its contribution, is more analytical. It relates to the name of places and combinesgeographical imaginary with cultural historic. Finally, the third part is intended to be amethodological milestone, or the highlighting of toponymic literality in the French-speakingfiction of Central Africa.
Keywords: African Research